Utilization of squid by-product hydrolysate as an alternative feed ingredient in the diet of black tiger shrimp (Penaeus monodon) - Pan, Maila Villanueva (2022)
The constant increase in the production of fish resources also entails the generation of large volume of wastes particularly in fish processing industry. This is also similar to squid peocessing industry, where in a large fraction of the raw materiials is usually downgraded into waste processing by-products. Therefore, the present study tried to develop a utility for this processing by-products to fully maximize the utilization of this resource, and alleviate the concerns on waste disposal. The potential of squid by product hydrolysate (SH) as an alternative feed ingredient in the diet of black tiger shrimp (Penaeus monodon) has been evaaluated. Three studies were conducted to assess the efficacy of SH as a fish meal replacement, as a feeding attraactaant, and as a dietary prebiotic. Hydrolysate from squid by-products (head, tentacles, viscera, fins, and skin) was produced by enzymatic hydrolysis using bromelain and were used in the experiments. The first trial was conducted for eight weeks wherein SH replaced fish meal in a plant protein-based diet of P. monodon at increasing levels of 0, 25, 50, 75, and 100%. Hepatopancreas histology and and lactic acid bacterial growth were aalso evaluated. The hydrolysate used in the present study was produced at an optimum dose of bromelain at 1 % enzyme to substrate ratio that resulted in a hydrolysate product exhibiting a 57.89 ± 1.61 % degree of hydrolysis. The hydrolysate produced comprised 90.36 ± 0.25 % protein, 5.95 ± 0.07 % lipid, and 3.26 ± 0.05 % ash, with a chemical score index of 6.16 %, with arginine and tryptophan (18.26 %) as the limiting amino acids, an essential amino acid index of 0.74, essential and non-essential amino acid ratio of 0.86 and a molecular weight estimated at 3.79 kDa.The results of the trial showed that the shrimp fed with 25% fish meal replacement with SH exhibited the highest growth rate among the treatments (per cent weight gain, P<0.05 ; specific weight gain, P<0.05). The growth enhancement was attributed to increased feed intake (P<0.05), lipid retention (P<0.05), and gut lactic acid bacteria proliferation (P<0.05). Shrimp fed diets with 100% fish meal replacement with SH showed comparable growth with the control group (P>0.05). Histological analysis showed that B-cells dominated the hepatopancreas of the control group while R-cells were observed to increase with increasing supplementation of dietary SH). The second study evaluated the combination of SH with low level dietary fish meal in a plant protein-based diet of P. monodon. The study was done in a 3 x 3 factorial experiment with formulated plant protein-based diets containing o, 5 and 10 % fish meal supplemented with SH at 0, 0.5, and 1 %. A treatment with full meal based diet was also prepared to serve as the positive control. The experimental diets were tested for attractability, palatability and fed to shrimp for eight weeks to evaluate growth, digestive enzyme activities, transcription of muscle-growth-related genes, and muscle morphometry. Results indicate that diet attractability were higher in diets with 10 % fish meal level(P<0.05) and0.5 % SH supplementation (P<0.05). Further, diets with 5 % fish meal levels with 0.5% or without SH supplementation and full plant protien-based diets incorporated with 0.5 and 1 % SH were more palatable (P<0.05) to shrimp. The highest growth (per cent weight gain, P<0.05); specific growth rate, P<0.05) was observed in shrimp fed with diets without fish meal but supplemented with 1 % SH. This enhanced growth performance was attributed to significant enhancement of feed intake (fish meal levels, P<0.05), efficient feed conversion (P<0.05), improved protein efficiency ratio (SH levels, P<0.05), and nutrient retention (protein retention, SH levels : P<0.05; lipid retention, P<0.05, enhancement of digestive enzyme activities (P<0.05), up-regulation of muscle growth-related genes (GLUT-1, P<0.05; tor, P<0.05; s6k, P,0.05; 4e-bp, P<0.05; a-actin, P<0.05), and increased muscle men fiber area (P<0.05).The results of the trial showed that the shrimp fed with 25% fish meal replacement with SH exhibited the highest growth rate among the treatments (per cent weight gain, P<0.05 ; specific weight gain, P<0.05). The growth enhancement was attributed to increased feed intake (P<0.05), lipid retention (P<0.05), and gut lactic acid bacteria proliferation (P<0.05). Shrimp fed diets with 100% fish meal replacement with SH showed comparable growth with the control group (P>0.05). Histological analysis showed that B-cells dominated the hepatopancreas of the control group while R-cells were observed to increase with increasing supplementation of dietary SH). The second study evaluated the combination of SH with low level dietary fish meal in a plant protein-based diet of P. monodon. The study was done in a 3 x 3 factorial experiment with formulated plant protein-based diets containing o, 5 and 10 % fish meal supplemented with SH at 0, 0.5, and 1 %. A treatment with full meal based diet was also prepared to serve as the positive control. The experimental diets were tested for attractability, palatability and fed to shrimp for eight weeks to evaluate growth, digestive enzyme activities, transcription of muscle-growth-related genes, and muscle morphometry. Results indicate that diet attractability were higher in diets with 10 % fish meal level(P<0.05) and0.5 % SH supplementation (P<0.05). Further, diets with 5 % fish meal levels with 0.5% or without SH supplementation and full plant protien-based diets incorporated with 0.5 and 1 % SH were more palatable (P<0.05) to shrimp. The highest growth (per cent weight gain, P<0.05); specific growth rate, P<0.05) was observed in shrimp fed with diets without fish meal but supplemented with 1 % SH. This enhanced growth performance was attributed to significant enhancement of feed intake (fish meal levels, P<0.05), efficient feed conversion (P<0.05), improved protein efficiency ratio (SH levels, P<0.05), and nutrient retention (protein retention, SH levels : P<0.05; lipid retention, P<0.05, enhancement of digestive enzyme activities (P<0.05), up-regulation of muscle growth-related genes (GLUT-1, P<0.05; tor, P<0.05; s6k, P,0.05; 4e-bp, P<0.05; a-actin, P<0.05), and increased muscle men fiber area (P<0.05). The third experiment evaluated the interactive effects of probiotics and SH supplementations in a plant protein-based diet of P. monodon. The experimental shrimp were fed with plant proetin-based diets containing 0.5, 1, and 2 % SH in tandem with probiotics supplementation at a dose of 0 and 10⁻⁹ Bacillus subtilis BF12 g⁻¹ diet. Experimental treatments with plant protein-based diet, without the SH supplementation, and a full fish meal-based diet were also formulated to serve as the negative and positive controls, respectively. Growth performance, immune-related and gut pro-inflammatory gene transcriptions, gut histomorphology and gut bacterial counts (total bacteria, total Vibrio, yellow Vibrio, and green Vibrio) were evaluated as response indices. Results suggest that the growth response of shrimp fed with plant protein-based diet at 0.5 % SH and B. subtilis BF12 supplementation was higher than the full fish meal control group without B. subtilis BF12 addition (percent weight and specific growth rate, P.0.05) and comparable to Fishmeal control with B. subtilis BF12 supplementation (per cent weight and specific growth rate, P,0.05). The improvement in the growth of shrimp was associated with better feed conversion ratio (SH levels, P<0.05), enhanced protein efficiency ration (P,0.05), improved protein (P,0.05) and lipid (P<0.05) retentions, and up-regulation of heat shock protein 70 (P<0.05). However, protease and a-amylase activities were higher in diets supplemented with 2 % SH (SH levels, P<0.05). while lipase was higher in shrimp given with 1% SH supplementation (SH level, P<0.05). This increase in digestive enzyme activities were attributed to the improved intestinal health of shrimp as exhibited in the improvement of intestinal villi height (P<0.05). In the transcription of the immune-related genes, prophenoloxidase was influenced by SH supplementation (p<0.05),while RAB-6a transription was found higher in a plant protein-based diet supplemented with 2% SH without B. subtilis BF12 supplementation (P<0.05). The expression of lipopolysaccharide-induced tumor necrosis factor-alpha factor gene was influenced by both SH supplementation and probiotic application without any interactions. It was observed to be higher n the diet with 0.5% SH supplementation (P<0.05) but it decreased with B. subtilis BF12 supplementation (P<0.05). The potential of SH as prebiotics has been observed in the present study and supported the proliferation of probiotics. The growth of green Vibrios has also been significantly decreased during the whole experiment in the diet with 2% SH supplementation (P<0.05). Collectively, these studies indicate that SH could completely replace fish meal in the diet of P. monodon, could be used as a supplement in P. monodon plant protein-based diet, and could serve as an effective prebiotic to enhance the performance of p. monodon when fed with plant protein-based diets. The growth enhancing effects of SH could be attributed to its bioactivity to promote muscle growth, improvement of gut health and activation of immune-related genes. The use of SH could be aa practical approach to lessen the aquaculture dependencenon the use of fish meaal as feed ingredient and to enhance the feed value of plant protein-based dietary formulations.
Dissertation (Doctor of Philosophy in Fisheries) -- Miagao, Iloilo : University of the Philippines Visayas, August 2022.